Effects of task complexity on the oral production of Chinese learners of Portuguese as a foreign language. (31st August 2018) - Santos, Sara
This study aims to investigate the effects of task complexity on the oral performance of Chinese learners of European Portuguese as a foreign language (PFL). In the current investigation, the cognitive task demands were manipulated along the resource-directing and resource-dispersing dimensions of the Triadic Componential Framework (Robinson, 2001, 2003, 2005, 2010, 2011, 2015 ). The variables chosen were respectively ±few elements and ±planning time. Using a 2 × 2 design, 39 university learners of PFL performed two monologic information-giving oral tasks: a simple task (two elements) and a complex task (six elements). Half of the learners ( n = 19) were given pre-task planning time, but for the other half ( n = 20) the planning time was removed. The order of the tasks was counterbalanced. The participants' output was analysed by general and specific measures of syntactic complexity and accuracy, lexical diversity and fluency (CALF). Pre-task planning time had significant effects on accuracy. Increasing the number of elements of the task led to greater accuracy and lexical diversity and longer clause length. There were no significant effects on fluency. These findings partially support Robinson's Cognition Hypothesis. To the best of our knowledge, this study is the first CALF study to measure the oral performance of learners of PFL. These results provide new insights for research and learning in the field of instructed second language acquisition (ISLA).